2021
DOI: 10.3390/ijerph18157741
|View full text |Cite
|
Sign up to set email alerts
|

Are Long-Distance Walks Therapeutic? A Systematic Scoping Review of the Conceptualization of Long-Distance Walking and Its Relation to Mental Health

Abstract: Long-distance walking is an ancient activity practiced across cultures for many reasons, including the improvement of one’s health. It has even been suggested that long-distance walking may be considered a form of psychotherapy. This scoping review examined the relationship between long-distance walking and mental health among adults. Publication trends and definitions were also examined, and the reason why long-distance walking may have therapeutic effects was discussed. Systematic searches in three online da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Humans move with their feet to explore environments, look for food, escape from threats, and communicate with others. Walking is a basic human activity that improves human physical and mental health [1]- [3]. Factors such as feasibility, accessibility, safety, comfort, and pleasure affect or can be limiting factors to walking [4].…”
Section: Introductionmentioning
confidence: 99%
“…Humans move with their feet to explore environments, look for food, escape from threats, and communicate with others. Walking is a basic human activity that improves human physical and mental health [1]- [3]. Factors such as feasibility, accessibility, safety, comfort, and pleasure affect or can be limiting factors to walking [4].…”
Section: Introductionmentioning
confidence: 99%
“…Important physiological characteristic of hiking is the regular pace and sensory richness, including proprioceptive input on varying undergrounds. A meta-analysis of 26 studies on long-distance hiking revealed a positive association with mental health, most notably stress reduction, but less clear for general wellbeing (Mau et al, 2021).…”
Section: Examples Of Body-mind Life-style Activities Lead the Way Hikingmentioning
confidence: 96%
“…That hiking exposes to an experience of nature is considered a central element [see the extensive narrative review by Mitten (2009)]. Another aspect that is considered essential is the room the that long-distance hiking provides for personal reflection (Mau et al, 2021).…”
Section: Examples Of Body-mind Life-style Activities Lead the Way Hikingmentioning
confidence: 99%
“…Walking is the most common moderate-intensity PA reported among adults, 10 and it is strongly associated with good health and quality of life. 11 Treadmill walking is a common and important method for individuals with sedentary behavior, elderly, and stroke patients to engage in PA and rehabilitation training indoors. Monitoring the treadmill walking EE in those individuals can provide an effective tool for active health management, evaluating the body’s health and physiological status, tracking changes in aerobic fitness, and investigating dose-response relationships.…”
Section: Introductionmentioning
confidence: 99%